Assisting the bride and groom in performing Saptapadi - Mumbai Archive Project Team (Jio Institute, 2024)
During the haldi (turmeric) ceremony, the mami (wife of maternal uncle) and other close relatives assist the bride and groom in performing pheras or saptapadi (ritual of circumambulation around a sacred object). They carry a kalash (pot) containing coconut and mango leaves in their hands.